English Language Needs Analysis for Islamic Economic Law Students in Indonesian Higher Education: A Case Study at Institut Syekh Abdul Halim Hasan Binjai - Mutia Hafifah; Asmayani Asmayani (MAN 4 Kota Pekanbaru, 2026)
English proficiency is increasingly important for students of Islamic Economic Law, yet English instruction in many Islamic higher education institutions remains oriented toward General English rather than English for Specific Purposes (ESP). This study aimed to identify the English language needs of Islamic Economic Law students at Institut Syekh Abdul Halim Hasan Binjai. A mixed-methods case study was conducted involving 35 undergraduate students. Data were collected through questionnaires and semi-structured interviews and analyzed using descriptive statistics and thematic analysis. The findings indicate that legal English vocabulary was the highest learning priority (42.9%), followed by academic reading (25.7%), professional writing (14.3%), speaking (11.4%), and listening (5.7%). Students also preferred authentic learning materials related to Islamic banking, commercial law, contracts, and dispute resolution, as well as interactive learning activities such as case studies, role plays, group discussions, and problem-based learning. The study concludes that English instruction should be redesigned based on ESP principles by integrating discipline-specific vocabulary, authentic legal materials, and professional communication tasks to better support students’ academic achievement and career preparation.